2020
DOI: 10.1155/2020/7543930
|View full text |Cite
|
Sign up to set email alerts
|

Could Serum TSH Levels Predict Malignancy in Euthyroid Patients Affected by Thyroid Nodules with Indeterminate Cytology?

Abstract: Background. Serum TSH levels in the upper-normal range were reported to be associated with increased risk of thyroid malignancy. However, measurement of TSH levels is currently not recommended for assessing the risk of malignancy in patients with newly diagnosed thyroid nodules. Objective. To evaluate a possible relationship between the serum levels of TSH and the histological outcome of patients undergoing thyroidectomy for thyroid nodules with indeterminate cytology. Materials and Methods. We collected the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…However, patients with malignancy exhibited lower mean serum TSH levels than patients with benign pathology (3.2 ± 5.7 µIU/L vs. 3.7 ± 12.9 µIU/L; shown in Table 5). Previous studies have also demonstrated correlations between serum TSH concentrations and thyroid nodule malignancy, reporting the risk of malignancy to increase with preoperative TSH levels >2.7 µIU/L [44], above the population mean [45], in the upper quartile [46], and within the normal range [47]. However, despite the median association between serum TSH concentration and nodules harboring malignancy in this study being statistically significant ( p = 1.58e−3), the application of mild elevation in TSH as an independent, clinically relevant risk factor of malignancy is low.…”
Section: Discussionmentioning
confidence: 99%
“…However, patients with malignancy exhibited lower mean serum TSH levels than patients with benign pathology (3.2 ± 5.7 µIU/L vs. 3.7 ± 12.9 µIU/L; shown in Table 5). Previous studies have also demonstrated correlations between serum TSH concentrations and thyroid nodule malignancy, reporting the risk of malignancy to increase with preoperative TSH levels >2.7 µIU/L [44], above the population mean [45], in the upper quartile [46], and within the normal range [47]. However, despite the median association between serum TSH concentration and nodules harboring malignancy in this study being statistically significant ( p = 1.58e−3), the application of mild elevation in TSH as an independent, clinically relevant risk factor of malignancy is low.…”
Section: Discussionmentioning
confidence: 99%
“…Serum TSH levels in the upper-normal range were recently associated with an increased risk of thyroid malignancy in patients affected by thyroid nodules with indeterminate cytology and proposed as an easily performed additional tool for decision-making in patients with indeterminate cytological findings [ 11 ]. Accordingly we added TSH levels, together TLG to RFs (first-order and shape PyRadiomics parameters comprised SUVmax, SUVmean and MTV) in our analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The relationship between RoM and serum TSH in euthyroid individuals with cytologically indeterminate nodules corroborates this observation. A recent study showed that among 378 euthyroid patients the RoM was 9.8% for TIR3A nodules and 27.3% for TIR3B nodules (Cappelli et al 2020). However, in the subgroup with TSH in the lower quartile (0.4-1.42 mIU/L), the RoM was significantly lower, 5.9% for TIR3A and 12% for TIR3B (Cappelli et al 2020), possibly reflecting a higher probability of the nodules being autonomous in this TSH quartile.…”
Section: Scintigraphy With 123 I or 99m Tcmentioning
confidence: 95%